Effectiveness of Lemongrass Essential Oil Therapy Combined with Foot Marble Exercises on Foot Sensory Function in Patients with Type 2 Diabetes - Mulfianda, Riyan; Tharida, Maimun; Talitha Arista (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Background: Peripheral neuropathy is one of the most common chronic complications of Type 2 Diabetes Mellitus (T2DM), characterized by decreased sensory nerve function, numbness, and high risk of foot ulceration. Non-pharmacological foot care interventions, including foot exercises and essential oils, are increasingly recognized as complementary treatments for improving peripheral nerve sensitivity. Objective: This study aims to evaluate the effectiveness of combining Lemongrass Essential Oil (ESSOL) massage and marble-based foot exercises in improving foot sensitivity among patients with T2DM. Methods: A quasi-experimental pretest–posttest design with a control group was employed, involving 40 respondents selected through inclusion and exclusion criteria. Participants were divided into intervention (n = 20) and control (n = 20) groups. Foot sensitivity was assessed using the 10 g Semmes-Weinstein monofilament test before and after the intervention. Data were analyzed using appropriate statistical tests with α < 0.05. Results: There was a significant improvement in foot sensitivity in the intervention group compared to the control group (p < 0.05). The findings indicate that the combined intervention effectively enhances peripheral sensory response in individuals with T2DM. Conclusion: The combination of ESSOL massage and marble foot exercises is an effective non-pharmacological strategy to improve foot sensitivity among patients with T2DM and has the potential to prevent diabetic foot complications.